Making the Ethical Transition in South Africa: Acquiring Human Bodies for Training in Anatomy. Issue 3 (4th September 2018) - Kramer, Beverley; Hutchinson, Erin F.; Brits, Desiré M.; Billings, Brendon K.
Abstract : While dissection remains the method of choice for teaching human anatomy, ethical requirements for obtaining cadavers has made the process of acquiring human bodies more strenuous for institutions. In Africa and at the School of Anatomical Sciences in South Africa, dependence on unclaimed bodies has been prevalent. The aim of the present study was to determine whether more rigorous application of ethical consent has altered the provenance of the cadavers in the School of Anatomical Sciences, University of the Witwatersrand. The numbers of bequeathed/donated/unclaimed cadavers received over the period 2013–2017, as well as their sex and population affinity were analyzed. The majority (96.8%) of the cadavers dissected over the period were from bequests/donations. Marginally more females than males were available. In addition, the population affinity of the cadavers had changed from a majority of South African African (unclaimed) bodies to a majority of South African White (bequest/donated) bodies. The study shows that even with ethical constraints it is possible to transition from the use of mainly unclaimed bodies to the acquisition of bequeathed/donor bodies. However, there may be challenges in relation to anatomical collections in the School as few of the bequest/donated cadavers remain in the School to be added to the collections. These changes also affect the demographics of the Schools' collections.